MICRO-APARTMENT IN PONTIANAK - Dania, Al-Yakoob; Zain, Zairin; Pebriano, Valentinus (JMARS: Jurnal Mosaik Arsitektur, 2021)
As the world population, the majority of Indonesian’s town all knows an increase of their population that results in an augmentation of the housing needs. What is called Micro-housing is a new global trend that targets a younger worker part of the population and also a newly married couple that doesn’t have children yet. Indeed, this part of the population is in need to find house or apartment close to their workplace, close to the transportation of the city but also close to all the other town facilities like hospitals, restaurant, stores. This desire of finding a house or apartment in a strategic location known as the center of a town tends to increase but the available spaces to build more houses tend to decrease. That is why one of the solutions to this space problem is micro-housing; this type of new housing will allow responding to this problem of available space. This design project is not only about reducing space, but it is also focus on being able to design and create a layout space that responds to the multiple needs of the tenant by using multiple techniques in the design layout but also using transformable and foldable pieces of furniture.